CONSTRUCTION AND TECHNOLOGICAL CHARACTERISTICSOF WIDE BANDGAP SEMICONDUCTORS SENSORS - V. S. Volchek; D. HA. Dao; I. Yu. Lovshenko; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The development and research of new constructive solutions, materials and technologies for sensor systems production is an actual problem. The transistor with high electron mobility (HEMT) is increasingly being used in such systems. The device-technological simulation of the characteristics of HEMT, based on AlGaN / GaN using different substrate materials has implemented. The influence of the percentage of Al and Ga in combination Alх Gaх-1N on the characteristics of considered unit has studied.